Use of Electronic Medical Records for Research: New Ethical Challenges and Possible Solutions - Meneses-Oliveira, Carlos (2019)
Some clinicians feel that Ethics Committees act as a blockade to observational clinical studies. In the case of retrospective studies some have tried to solve this problem by reducing this sensitive data to simple administrative data in the hands of the government. Others see the new European General Data Protection Regulation 2016/679 (European Union) as being more liberal than the Portuguese Law nº 21/2014, April 16th (Clinical Research Law). Both solutions presume participant consent from his / her silence, even if nobody truly tried to specifically inform him / her. Such views do collide with the guarantees of protection of patient’s ethical rights. In this article we propose an ethical alternative to those positions.